Comparación de la tipología de vivienda vernácula de adobe en los cantones Riobamba y Chambo - Alulema Garcés, Verónica Leonela (2023)
The objective of this research is to analyze, evaluate and compare the typology of vernacular adobe housing in the cantons of Riobamba and Chambo recognizing the importance of Andean architecture in rural areas, conducting qualitative research that collects and processes information through freehand architectural plans and valuation sheets. The six typologies by canton reflect the miscegenation of the country's vernacular architecture such as the use of portals and arcades, addition of tile, carpentry, and interior courtyards in some cases. They are similar in the site solution based on the user's need, housing is related to the environment, physical-environmental and sociocultural context of each place. They differ in formal and structural aspects depending on the climatic floor being predominantly the structure of adobe load-bearing walls in the Riobamba canton and a structure of wooden porticos with adobe masonry in the Chambo canton. The assessment indicates that 90% of the case studies have a high patrimonial value so they should be inventoried by the National Institute of Heritage and Culture of Ecuador.